2011
DOI: 10.1182/blood-2011-05-356535
|View full text |Cite
|
Sign up to set email alerts
|

HIV envelope-mediated, CCR5/α4β7-dependent killing of CD4-negative γδ T cells which are lost during progression to AIDS

Abstract: HIV infects and replicates in CD4؉ T cells but effects on host immunity and disease also involve depletion, hyper-activation, and modification of CD4-negative cell populations. In particular, the depletion of CD4-negative ␥␦ T cells is common to all HIV؉ individuals. We found that soluble or cell-associated envelope glycoproteins from CCR5-tropic strains of HIV could bind, activates the p38-caspase pathway, and induce the death of ␥␦ cells. Envelope binding requires integrin IntroductionHIV evades the immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 55 publications
3
50
0
Order By: Relevance
“…Consistent with previous studies, 13,27 we found the Vd2 T cells declined at least as rapidly as CD4 T cells in early HIV infection, accompanied by the decreased IPP-responsive cells in the CD16 -Vd2 T cell subset. However, with a strong capacity for degranulation, the CD16 + Vd2 T cells from the early-infected group maintained cytotoxic Vd2 T cells as the potentially efficient ADCC effectors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies, 13,27 we found the Vd2 T cells declined at least as rapidly as CD4 T cells in early HIV infection, accompanied by the decreased IPP-responsive cells in the CD16 -Vd2 T cell subset. However, with a strong capacity for degranulation, the CD16 + Vd2 T cells from the early-infected group maintained cytotoxic Vd2 T cells as the potentially efficient ADCC effectors.…”
Section: Discussionsupporting
confidence: 93%
“…They also observed the highest level of HIV envelope-induced cell death in Vd2 T cells when exposed to phosphoantigen, which suggests that phosphoantigen activation might be the reason for the specific loss of the Vc2Jc1.2 Vd2 T cell subpopulation. 27 This finding may partially explain the different status of the two functional Vd2 T cells in early HIV-1 infection: the preservation of the functional Vd2 T cells responding to Fc targets, but not to IPP, in early HIV-1infection was probably due to the barely phosphoantigen-activated CD16 + Vd2 T cell subset. A strong and consistent relationship between viral load and the level of either CD4 + or CD8 + T cell activation has been found during early HIV infection.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies indicate that HIV-1 envelope glycoprotein (Env) gp120 is capable of interacting with integrin α 4 β 7 to potentially increase viral infection (Arthos J, et al, 2008;Cicala C, et al, 2009;Darc M, et al, 2011;Li H, et al, 2011;Nawaz F, et al, 2011;Richardson S I, et al, 2013;Tjomsland V, et al, 2013). α 4 β 7 is expressed on lymphoid cells and mediates cell homing to gut-associated lymphoid tissue (GALT), the dominant site of CD4 + T cell depletion shortly after HIV-1 acquisition and local propagation (Berlin C, et al, 1993;Mehandru S, et al, 2004;Sattentau Q, 2008;Veazey R S, et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been reported that direct interaction of IPP-expanded ␥␦ T lymphocytes with R5 HIV-1 envelope results in CCR5-␣4␤7-mediated cell death, and this mechanism has been proposed to contribute to the depletion of this cell population in AIDS patients (14,47). In the present work, we report that the direct stimulation of freshly isolated ␥␦ T cells with infectious R5 HIV-1 virions before TCR engagement does not affect their capacity to become fully activated and to expand in response to antigens.…”
Section: Discussionmentioning
confidence: 99%